AN AUDIT OF HOSPITALISATION IN MYASTHENIA GRAVIS PATIENTS. Issue 11 (14th October 2015) - Maddison, Paul; Ghosh, Rukmini
Abstract : Myasthenia gravis (MG) may cause acute, profound neurological illness, not infrequently requiring hospital admission, associated with significant morbidity and rarely mortality, despite effective immunosuppressive treatments. The reasons why patients with MG require hospital admission are not clear, although an audit of MG admissions conducted in Manchester identified early bulbar symptoms as predictive of increased risk of hospital admission. We aimed to replicate the Manchester audit in Nottingham, UK, to identify the factors responsible for admission that may be common to different UK centres. There were 124 admissions in 94 MG patients (2002–2012). Commonest reason for admission was first diagnostic presentation in 34 patients (34/124 admissions, 27%), with MG exacerbation resulting in admission in a further 32 patients (45/124 admissions, 36%). Triggers for exacerbation of MG were mostly unknown (50%), with 41% thought to be due to infection, and 6% due to reduction in steroid dose. In common with the previous UK audit, steroid doses in the 4 weeks prior to admission for MG relapse were only increased in 4/15, and unchanged in 7/15, despite all suffering bulbar symptoms. In accordance with other data, we have found that worsening bulbar symptoms, especially in the elderly population, are a risk for admission.